New orchids in the flora of Vietnam Ⅳ (Orchidaceae, Aeridinae) - Averyanov, Leonid V.; Thai, Tran Huy; Truong, Ba Vuong; Nguyen, van Canh; Nguyen, Tuan Hoang; Maisak, Tatiana V.; Nguyen, Khang Sinh; Nguyen, van Khuong (Phytotaxa, 2022)
This paper presents new data on the orchid diversity of Vietnam obtained in 2015–2021. It contains descriptions of three new species (Cleisostoma furcatum, Malleola micrantha, Schoenorchis hungii), one new variety (Chiloschista parishii var. minutiflora) and one new form (Cleisostoma furcatum forma albiflora). Additionally six species, Ascocentropsis malipoensis, Chiloschista sweelimii, Pomatocalpa undulatum, Trachoma rhopalorrhachis, Trichoglottis maculata, and Uncifera acuminata are newly recorded for Vietnam. The paper also provides an amended description of a very rare and poorly known species, Cleisostoma equestre. All studied taxa belong to subtribe Aeridinae (tribe Vandeae, subfamily Epidendroideae). The accepted plant name, main synonyms, data on type specimens, ecology, phenology and distribution, estimated IUCN Red List status, studied specimens, brief taxonomic notes, and illustrations are provided for each species listed.